Heart rate variability follow-up during COVID-19: A case report - Gutiérrez, Alejandro Figar (2022)
Background: To detect an early increase in the inflammatory response might prove to be vital for mitigating the deleterious effects of the disease over time. Case: A 52-year-old obese man with moderate asthma and hypertension, who developed COVID-19 and had moderate symptoms, used a wearable device to record heart rate variability (HRV) during his illness. He had low parasympathetic tone, which decreased daily until it reached almost 2 standard deviations (SD) below normal values at the end of the second week. His sympathetic tone increased from > 3 SD to > 5 SD. Conclusions: These findings suggest an altered modulation of the sympathetic and para-sympathetic nervous systems in COVID-19, such that the sympathetic tone is augmented and the parasympathetic tone is reduced. Population norms of COVID-19 infections should be further studied over the short-term and using 24 h HRV measurements.